GREEN ACCOUNTING AND ENVIRONMENTAL PERFORMANCE AS DETERMINANTS OF FIRM VALUE: THE MEDIATING ROLE OF PROFITABILITY IN INDONESIAN MINING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (2020–2024) - Haninun Haninun; Aulia Malik; Khairudin Khairudin (PT. Saha Kreasi Indonesia, 2026)
This study investigates whether green accounting and environmental performance influence firm value, while examining profitability as an intervening variable among mining companies listed on the Indonesia Stock Exchange over the 2020–2024 period. A quantitative approach was employed using secondary data obtained from corporate annual reports, sustainability reports, and environmental performance disclosures. The research sample comprised 18 mining companies, resulting in 90 balanced panel observations. Green accounting was represented by a Global Reporting Initiative (GRI)-based disclosure index, environmental performance was assessed using the PROPER rating, profitability was measured by Return on Assets (ROA), and firm value was proxied by Tobin’s Q. The empirical analysis utilized a Fixed Effect Model selected through the Chow and Hausman tests, while the mediating role of profitability was examined using the Sobel test. The findings indicate that green accounting does not have a statistically significant effect on either profitability or firm value. Similarly, environmental performance does not significantly influence profitability or firm value. Profitability also fails to demonstrate a significant effect on firm value in the primary model and does not serve as a mediator in the relationship between green accounting, environmental performance, and firm value. Nevertheless, robustness analyses using logarithmic transformation and winsorization reveal a positive and significant relationship between profitability and firm value, whereas the effects of green accounting and environmental performance, as well as the indirect effects through profitability, remain statistically insignificant. These findings suggest that environmental practices within the mining sector have not yet been sufficiently translated into market-based firm value, while profitability remains a fundamental determinant of firm value.